Acrylic composite board with stable surface quality and preparation method and application thereof

By adding a barrier layer and coating reinforcement layer to the acrylic composite panel, the problem of unstable surface quality of acrylic bathtub products is solved, and higher flatness, brightness and mechanical properties are achieved.

CN116574365BActive Publication Date: 2025-03-18JINLING-DSM RESINS LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310547981.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-16
Publication Date
2025-03-18
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

The existing acrylic bathtub products have problems such as poor flatness, low brightness, obvious corrugation and many bubbles between layers, resulting in unstable surface quality.

Method used

Add a barrier layer to the acrylic composite panel and add color paste to the barrier layer, allowing the colorless acrylic panel to obtain any selectable color through the adhesion properties of the unsaturated polyester resin to the acrylic. The barrier layer is coated with a reinforcement layer to avoid direct contact between the fiberglass reinforcement layer and the acrylic plate.

Benefits of technology

The surface flatness, brightness and surface quality of the acrylic composite board are improved, corrugated and interlayer bubbles are reduced, bonding strength and heat resistance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004230262070000081
    Figure BDA0004230262070000081
  • Figure BDA0004230262070000091
    Figure BDA0004230262070000091
  • Figure BDA0004230262070000092
    Figure BDA0004230262070000092
Patent Text Reader

Abstract

The present invention provides an acrylic composite board with stable surface quality and a preparation method and application thereof, belonging to the technical field of composite board materials. The acrylic composite board comprises an acrylic board and a barrier layer and a glass fiber reinforced plastic reinforcing layer adhered to the surface in sequence. By adding a barrier layer to the acrylic composite board, color paste can be added to the barrier layer, and the colorless acrylic board can obtain any selectable color through the bonding performance of unsaturated resin and acrylic. After the barrier layer is coated with the reinforcing layer, direct contact between the glass fiber reinforced plastic reinforcing layer and the acrylic board is avoided, thereby avoiding the instability of the surface quality caused by the glass fiber reinforced plastic layer. The obtained acrylic composite board has high surface flatness, high brightness, low corrugation and high surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite board materials, and in particular relates to an acrylic composite board with stable surface quality and a preparation method and application thereof. Background Art

[0002] Acrylic, commonly known as organic glass, can be divided into transparent plates, translucent plates and colored plates. It is known as "plastic crystal". Acrylic has the advantages of strong corrosion resistance and high strength, so it is an excellent material for making furniture. Acrylic bathtubs have unique characteristics of lightness, low thermal conductivity, easy cleaning and skin-friendly. They are also cheap and have simple molding processes. They are now widely used in homes, hotels and various bathing places, and are gradually replacing traditional cast iron and ceramic bathtubs. The social demand is increasing year by year.

[0003] An acrylic bathtub is a bathtub made of PMMA plastic material. The body of an acrylic bathtub generally includes a surface layer (acrylic layer) and an inner layer (glass fiber resin reinforcement layer). The production usually includes the following steps: 1. The body of the acrylic bathtub is formed by high-temperature vacuum forming; 2. A layer of reinforced fiberglass is made on one side of the body of the acrylic bathtub through hand lay-up or spraying technology to increase the supporting strength of the body of the acrylic bathtub.

[0004] Due to the unique advantages of acrylic bathtubs over other bathtubs, research and development of high-performance acrylic bathtubs has become a trend. Chinese patent CN110435272A discloses an acrylic composite board with stable surface quality and sanitary ware, including a panel layer, a functional layer, and a lining layer, wherein the panel layer is an acrylic layer embedded with a mineral-doped non-woven fabric, the functional layer is a honeycomb resin layer containing composite fiber materials, and the lining layer is a glass fiber reinforced unsaturated polyester resin layer. By making adaptive improvements to the raw materials and structure of the multi-layer board, it has excellent auxiliary effects, significantly improved physical and chemical properties, and water can flow through the inside of the board as needed, with good filtering and health effects, and good applicability. Chinese patent CN111320730A discloses a method for preparing a wear-resistant self-repairing acrylic material for a bathtub, wherein acetone cyanohydrin, sulfuric acid and methanol are used as raw materials to prepare methyl methacrylate, and system a is prepared using zirconium dioxide as a wall material and a small amount of methyl methacrylate as a core material; system b is prepared using silicon dioxide as a wall material and nano zinc powder as a core material; systems a and b are mixed and calcined to obtain a modified product; the modified product is added to a large amount of methyl methacrylate, and polymerized under the catalysis of benzoyl peroxide to obtain acrylic; inorganic fillers are added to acrylic monomers to improve the wear resistance of the finished acrylic product, and the inorganic fillers are coated with self-repairing substances, so that when the acrylic is worn and cracked, the wall material breaks and releases the self-repairing substances therein, which can not only self-repair the cracks, but also improve the water resistance of the material.

[0005] However, as people's living standards improve, they have higher and higher requirements for the quality of acrylic bathtub products, especially the appearance. Today's acrylic bathtub products still have shortcomings: such as poor flatness, low brightness, obvious ripples, and many bubbles between layers. Therefore, the application of acrylic bathtub materials still has great limitations. Summary of the invention

[0006] The purpose of the present invention is to provide an acrylic composite board in view of the deficiencies in the prior art. A barrier layer is added to the acrylic composite board, color paste can be added to the barrier layer, and the colorless acrylic board can obtain any selectable color through the bonding performance of unsaturated polyester resin and acrylic; after the reinforcing layer is coated on the surface of the barrier layer, direct contact between the fiberglass reinforced plastic reinforcing layer and the acrylic board is avoided, thereby improving the surface quality of the acrylic composite board.

[0007] Unsaturated polyester resin has high bonding strength, high heat resistance, and excellent mechanical properties. The resulting acrylic composite board has high surface flatness, high brightness, low corrugation, and high surface quality.

[0008] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0009] On the one hand, an unsaturated polyester resin comprises polyester, a crosslinking agent, fumed silica and an auxiliary agent; wherein the crosslinking agent comprises styrene, hydroxyethyl methacrylate and 2-phenylpropylene in a mass ratio of 26-35:3-9:0-2.

[0010] As a preferred embodiment of the present invention, the crosslinking agent comprises styrene, hydroxyethyl methacrylate and 2-phenylpropylene in a mass ratio of 26-35:8-9:0-2.

[0011] As a further preferred embodiment of the present invention, the crosslinking agent comprises styrene and hydroxyethyl methacrylate in a mass ratio of 26:9.

[0012] In the present invention, the polyester comprises diol, dibasic acid or dibasic acid anhydride and dicyclopentadiene in a mass ratio of 20-40:20-25:3-6.

[0013] As a preferred embodiment of the present invention, the polyester comprises diol, dibasic acid or dibasic acid anhydride and dicyclopentadiene in a mass ratio of 30:22:5.

[0014] As a preferred embodiment of the present invention, the diol is any one of 1,2-propylene glycol, 1,3-propylene glycol, ethylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, and neopentyl glycol, or a combination of several thereof, and is further preferably a mixture of 1,2-propylene glycol, dipropylene glycol or diethylene glycol and ethylene glycol; the mixing mass ratio of the 1,2-propylene glycol, dipropylene glycol or diethylene glycol, and ethylene glycol is 2-4:1.5-2.5:1, and is further preferably 3:2:1.

[0015] As a preferred embodiment of the present invention, the dibasic acid or dibasic acid anhydride is any one of oxalic acid, succinic acid, adipic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, phthalic anhydride, maleic anhydride or a combination of several thereof, more preferably a mixture of phthalic anhydride and maleic anhydride; the weight ratio of phthalic anhydride to maleic anhydride is 1:0.5-2, more preferably 1:0.7.

[0016] In the present invention, the particle size of the fumed silica is 0.2-0.5 μm.

[0017] In the present invention, the auxiliary agents include accelerators, defoamers and surfactants.

[0018] As a preferred embodiment of the present invention, the accelerator is any one or a combination of cobalt isooctanoate, potassium isooctanoate, copper isooctanoate, cobalt naphthenate, copper naphthenate, dodecyl mercaptan, benzophenone, benzoin and other organic acid metal salts, and is more preferably a combination of cobalt isooctanoate and copper isooctanoate; the weight ratio of cobalt isooctanoate to copper isooctanoate is 1:0.1-0.5, and is more preferably 1:0.16.

[0019] As a preferred embodiment of the present invention, the defoaming agent is a fatty acid and fatty acid ester, amide, phosphate, polyether, polyether-modified polysiloxane defoaming agent; further preferred is lauric acid, palmitic acid, fatty acid glyceride, stearic acid, polyoxypropylene polyoxyethylene ether, polyoxyethylene polyoxypropylene glycerol ether, glycerol polyoxyethylene ether, or a mixture of any one or more thereof.

[0020] As a preferred embodiment of the present invention, the surfactant is a nonionic surfactant or an amphoteric surfactant, and is further preferably any one of lauryl alcohol polyoxyethylene ether, isooctyl alcohol polyoxyethylene ether, ethoxylated fatty acid methyl ester, alkylphenol polyoxyethylene ether, fatty amine polyoxyethylene ether, dodecyl ethoxy sulfobetaine, and dodecyl sulfopropyl betaine or a mixture of several thereof.

[0021] In the present invention, the unsaturated polyester resin comprises the following components by weight: 45-65% polyester, 30-50% crosslinking agent, 0.2-3% fumed silica, 0.001-0.1% accelerator, 0.1-2% defoamer and the remainder surfactant.

[0022] As a preferred embodiment of the present invention, the unsaturated polyester resin comprises the following components by weight: 50-60% polyester, 34-45% crosslinking agent, 0.2-1% fumed silica, 0.001-0.1% accelerator, 0.1-2% defoamer and the remainder surfactant.

[0023] As a further preferred embodiment of the present invention, the unsaturated polyester resin comprises the following components by weight: 57% polyester, 35% crosslinking agent, 0.6% fumed silica, 0.0174% accelerator, 0.2% defoaming agent and the remainder surfactant.

[0024] In another aspect, the method for preparing the unsaturated polyester resin comprises the following steps:

[0025] 1) Polycondensing diol, dibasic acid or dibasic acid anhydride with dicyclopentadiene to obtain polyester;

[0026] 2) The polyester obtained in step 1) is mixed and dispersed evenly with a crosslinking agent, fumed silica and an auxiliary agent to obtain the unsaturated polyester resin.

[0027] As a preferred embodiment of the present invention, in step 1), the polycondensation temperature is 200-230°C, more preferably 210-220°C.

[0028] As a preferred embodiment of the present invention, in step 2), the dispersion temperature is 50-80°C, more preferably 50-70°C.

[0029] On the other hand, an acrylic composite board with stable surface quality comprises: an acrylic board and a barrier layer and a fiberglass reinforced layer adhered to the surface in sequence; wherein the barrier layer and the fiberglass reinforced layer contain the unsaturated polyester resin described above.

[0030] As a preferred embodiment of the present invention, the barrier layer further comprises a curing agent; the curing agent is a peroxide, aliphatic amine, or amide amine curing agent, and is further preferably any one of N-aminoethylpiperazine, dibenzoyl peroxide, methyl ethyl ketone peroxide, and cyclohexanone peroxide, and is more preferably methyl ethyl ketone peroxide; the added amount of the curing agent is 1-5% of the weight of the unsaturated polyester resin, and is further preferably 2%.

[0031] As a preferred embodiment of the present invention, according to customer needs, the barrier layer is further added with color paste, and the addition amount of the color paste is 0-20% by weight of the unsaturated polyester resin, and more preferably 7%.

[0032] As a preferred embodiment of the present invention, the FRP reinforcement layer further comprises calcium carbonate powder, glass fiber chopped strand mat and a curing agent.

[0033] As a further preferred embodiment of the present invention, in the FRP reinforcement layer, the particle size of the calcium carbonate powder is 300-350 mesh, and more preferably 320 mesh.

[0034] As a further preferred embodiment of the present invention, in the FRP reinforcement layer, the gram weight of the glass fiber chopped strand mat is 300-500 g / m 2 , more preferably 400g / m 2 .

[0035] As a further preferred embodiment of the present invention, in the FRP reinforcement layer, the curing agent is the same as the curing agent in the barrier layer.

[0036] As a further preferred embodiment of the present invention, the FRP reinforcement layer comprises the following components in parts by weight: 100 parts by weight of unsaturated polyester resin, 100-140 parts by weight of calcium carbonate powder, 280-320 parts by weight of glass fiber chopped strand mat, and 1-3 parts by weight of curing agent.

[0037] More preferably, the FRP reinforcement layer comprises the following components by weight percentage: 100 parts by weight of unsaturated polyester resin, 120 parts by weight of calcium carbonate powder, 300 parts by weight of glass fiber chopped strand mat, and 1.5 parts by weight of curing agent.

[0038] As a preferred embodiment of the present invention, the acrylic plate has a thickness of 1-2 mm.

[0039] As a preferred embodiment of the present invention, the thickness of the barrier layer is 0.2-0.6 mm.

[0040] As a preferred embodiment of the present invention, the thickness of the fiberglass reinforced plastics reinforcement layer is 0.2-2.5 mm.

[0041] On the other hand, the method for preparing the acrylic composite board with stable surface quality comprises the following steps:

[0042] 1) Applying a barrier layer: uniformly mixing the unsaturated polyester resin, the curing agent and the color paste, and applying the mixture on an acrylic plate to prepare a barrier layer;

[0043] 2) coating a glass fiber reinforced plastic reinforcing layer: the unsaturated polyester resin, calcium carbonate powder and curing agent are mixed and stirred evenly, and glass fiber chopped strand mat is added and mixed evenly to obtain a mixed coating liquid; then the coating liquid is coated on one side of the barrier layer of the acrylic plate obtained in step 1) to obtain a glass fiber reinforced plastic reinforcing layer, and after curing, the acrylic composite plate with stable surface quality is obtained.

[0044] As a preferred embodiment of the present invention, the coating method is hand lay-up or spraying.

[0045] On the other hand, the acrylic composite board with stable surface quality is used in the preparation of decorative boards and bathroom products.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] (1) The present invention adds a barrier layer to the acrylic composite board, adds color paste to the barrier layer according to customer needs, and uses the bonding performance of unsaturated resin and acrylic to allow the colorless acrylic board to obtain any selectable color;

[0048] (2) After the barrier layer is coated with the reinforcement layer, the FRP reinforcement layer is prevented from directly contacting the acrylic plate, thereby avoiding the instability of the surface quality caused by the FRP layer;

[0049] (3) The unsaturated polyester resin provided by the present invention, through the compounding of various components, gives the resin higher bonding strength, heat resistance and mechanical properties. The acrylic composite board prepared by the unsaturated polyester resin can be firmly bonded to the surface of the acrylic board and is not easy to fall off, and has a long service life. DETAILED DESCRIPTION

[0050] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of protection claimed in this application, and those skilled in the art can make various changes and modifications to the invention of this application based on the disclosed content, and they should also fall within the scope of protection claimed in this application.

[0051] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0052] Example 1

[0053] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0054] Polyester: propylene glycol 15%, diethylene glycol 10%, ethylene glycol 5%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0055] Crosslinking agent: styrene 35%, hydroxyethyl methacrylate 3%;

[0056] Fumed silica 0.6%;

[0057] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0058] Fatty acid glycerides: 0.2%;

[0059] Fatty amine polyoxyethylene ether balance.

[0060] The preparation method of the above unsaturated polyester resin comprises the following steps:

[0061] 1) Propylene glycol, diethylene glycol, ethylene glycol, phthalic anhydride, maleic anhydride and dicyclopentadiene are polycondensed at 220°C to obtain polyester;

[0062] 2) The polyester obtained in step 1) is mixed evenly with a crosslinking agent to form a solution, and an accelerator, fumed silica, fatty acid glyceride and fatty amine polyoxyethylene ether are added and dispersed evenly at 60° C. to obtain the unsaturated polyester resin.

[0063] Example 2

[0064] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0065] Polyester: propylene glycol 15%, diethylene glycol 10%, ethylene glycol 5%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0066] Crosslinking agent: styrene 26%, hydroxyethyl methacrylate 9%;

[0067] Fumed silica 0.6%;

[0068] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0069] Fatty acid glycerides: 0.2%;

[0070] Fatty amine polyoxyethylene ether balance.

[0071] The preparation method of unsaturated polyester resin is the same as that of Example 1.

[0072] Example 3

[0073] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0074] Polyester: propylene glycol 15%, diethylene glycol 10%, ethylene glycol 5%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0075] Crosslinking agent: styrene 33%, hydroxyethyl methacrylate 9%;

[0076] Fumed silica 0.6%;

[0077] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0078] Fatty acid glycerides: 0.2%;

[0079] Fatty amine polyoxyethylene ether balance.

[0080] The preparation method of unsaturated polyester resin is the same as that of Example 1.

[0081] Example 4

[0082] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0083] Polyester: propylene glycol 15%, dipropylene glycol 10%, ethylene glycol 5%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0084] Crosslinking agent: styrene 26%, hydroxyethyl methacrylate 8%, 2-phenylpropylene 2%;

[0085] Fumed silica 0.6%;

[0086] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0087] Fatty acid glycerides: 0.2%;

[0088] Fatty amine polyoxyethylene ether balance.

[0089] The preparation method of unsaturated polyester resin is the same as that of Example 1.

[0090] Example 5

[0091] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0092] Polyester: propylene glycol 13.5%, diethylene glycol 10%, ethylene glycol 6.5%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0093] Crosslinking agent: styrene 26%, hydroxyethyl methacrylate 9%;

[0094] Fumed silica 0.6%;

[0095] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0096] Fatty acid glycerides: 0.2%;

[0097] Fatty amine polyoxyethylene ether balance.

[0098] The preparation method of unsaturated polyester resin is the same as that of Example 1.

[0099] Example 6

[0100] Unsaturated polyester resin, calculated by weight percentage, comprises the following components:

[0101] Polyester: propylene glycol 16%, diethylene glycol 10%, ethylene glycol 4%, phthalic anhydride 13%, maleic anhydride 9% and dicyclopentadiene 5%;

[0102] Crosslinking agent: styrene 26%, hydroxyethyl methacrylate 9%;

[0103] Fumed silica 0.6%;

[0104] Accelerator: cobalt 2-octanoate 0.015%, copper 2-octanoate 0.0024%;

[0105] Fatty acid glycerides: 0.2%;

[0106] Fatty amine polyoxyethylene ether balance.

[0107] The preparation method of unsaturated polyester resin is the same as that of Example 1.

[0108] Comparative Example 1:

[0109] The difference between Comparative Example 1 and Example 2 is that the cross-linking agent is different. The cross-linking agent in Comparative Example 1 is 35% styrene.

[0110] Comparative Example 2

[0111] The difference between Comparative Example 2 and Example 2 is that the crosslinking agent is different. The crosslinking agent of Comparative Example 2 includes 25% styrene and 9% hydroxyethyl methacrylate.

[0112] Comparative Example 3

[0113] The difference between Comparative Example 3 and Example 2 is that the polyester is different. The polyester in Comparative Example 3 includes 25% propylene glycol, 5% ethylene glycol, 13% terephthalic acid and 9% maleic anhydride.

[0114] Comparative Example 4

[0115] The difference between Comparative Example 4 and Example 2 is that the polyester is different. The polyester in Comparative Example 4 includes: 15% diethylene glycol, 15% ethylene glycol, 13% maleic anhydride and 15% dicyclopentadiene.

[0116] Experimental Example 1

[0117] 20 g of the unsaturated polyester resin obtained in Examples 1-6 and Comparative Examples 1-5 were respectively mixed with 0.4 g of methyl ethyl ketone peroxide and coated on an acrylic plate. The thickness of the acrylic plate was 1.5 mm and the coating thickness was 0.5 mm. The bonding strength between the unsaturated polyester resin and the acrylic plate was tested using an Elcometer 506 adhesion tester. The test results are shown in Table 1.

[0118] Table 1. Bond strength of resins

[0119]

[0120]

[0121] As shown in Table 1, it can be seen from the comparison of Examples 1-3 and Comparative Examples 1-2 that limiting the ratio of styrene and hydroxyethyl methacrylate in the crosslinking agent can improve the bonding strength between the unsaturated polyester and the acrylic plate. It can be seen from Comparative Examples 2 and 4 that adding 2-phenylpropylene to the crosslinking agent slightly reduces the bonding strength between the obtained unsaturated polyester resin and the acrylic plate.

[0122] Experimental Example 2

[0123] 20 g of the unsaturated polyester resin obtained in Examples 1-6 and Comparative Examples 1-5 were respectively mixed with 0.4 g of methyl ethyl ketone peroxide and then cured into a 4 mm thick film. The heat deformation temperature and mechanical properties were tested according to GB / T 2567-2021. The results are shown in Table 2 below.

[0124] Table 2. Heat resistance and mechanical properties of resin

[0125]

[0126]

[0127] As shown in the results of Table 2, by comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that the selection of the cross-linking agent has a certain influence on the heat resistance and mechanical properties of the unsaturated polyester resin. Compared with a single cross-linking agent, a certain proportion of styrene and hydroxyethyl methacrylate are selected for compounding and use, and better mechanical properties can be obtained; the tensile strength and heat resistance of the unsaturated polyester resin obtained in Comparative Examples 3 and 4 are significantly lower than those in Examples 2 and 5-6, indicating that the unsaturated polyester resin provided by the present invention is beneficial to improving the mechanical properties and heat resistance of the resin by compounding the components in the polyester.

[0128] Example 7

[0129] The method for preparing an acrylic composite board with stable surface quality comprises the following steps:

[0130] 1) Preparation of barrier layer

[0131] 20 g of the unsaturated polyester resin obtained in Example 2 was mixed evenly with 1.4 g of black color paste and 0.4 g of methyl ethyl ketone peroxide, and coated on an acrylic plate to prepare a barrier layer with a thickness of 0.3 mm;

[0132] 2) Preparation of FRP reinforcement layer

[0133] 100g of the unsaturated polyester resin obtained in Example 2, 120g of calcium carbonate powder (particle size 320 mesh), and 1.5g of methyl ethyl ketone peroxide were mixed and stirred evenly, and 300g of glass fiber chopped strand mat (weight 400g / m 2) are mixed evenly; and then a glass fiber reinforced plastic reinforcement layer is coated on one side of the barrier layer of the acrylic plate obtained in step 1) with a thickness of 2 mm to obtain the acrylic composite plate with stable surface quality.

[0134] Example 8

[0135] The method for preparing an acrylic composite plate with stable surface quality is different from that of Example 7 in that the unsaturated polyester resin in the barrier layer is the unsaturated polyester resin obtained in Example 4.

[0136] Example 9

[0137] The method for preparing an acrylic composite plate with stable surface quality is different from that of Example 7 in that the unsaturated polyester resin in the glass fiber reinforced plastic reinforcement layer is the unsaturated polyester resin obtained in Example 4.

[0138] Example 10

[0139] The method for preparing an acrylic composite board with stable surface quality comprises the following steps:

[0140] 100 g of the unsaturated polyester resin obtained in Example 2, 120 g of calcium carbonate powder, and 1.5 g of methyl ethyl ketone peroxide were mixed and stirred evenly, and 300 g of glass fiber chopped strand mat was added and mixed evenly; then a glass fiber reinforced plastic reinforcement layer with a thickness of 2 mm was coated on one side of the acrylic board to obtain the acrylic composite board with stable surface quality.

[0141] Embodiment 11

[0142] The method for preparing an acrylic composite board with stable surface quality comprises the following steps:

[0143] 100 g of the unsaturated polyester resin obtained in Example 4, 120 g of calcium carbonate powder, and 1.5 g of methyl ethyl ketone peroxide were mixed and stirred evenly, and 300 g of glass fiber chopped strand mat was added and mixed evenly; then a glass fiber reinforced plastic reinforcement layer with a thickness of 2 mm was coated on one side of the acrylic board to obtain the acrylic composite board with stable surface quality.

[0144] By observing the acrylic composite panels with stable surface quality prepared by the methods described in Examples 7-11, it can be seen that in Examples 7-9, a barrier layer is added, and the surface of the acrylic composite panels obtained has a mirror effect, no obvious glass fiber texture, and fewer interlayer bubbles, and the surface quality of the acrylic composite panels is relatively high. However, in Examples 10 and 11, there is no barrier layer, and the glass fiber reinforced plastic layer is directly coated on the acrylic surface. The acrylic composite panels obtained have more interlayer bubbles and obvious glass fiber texture, and the surface quality of the acrylic composite panels is relatively low and unstable.

[0145] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here. The above embodiments are only used to illustrate the present invention, but not to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions also belong to the scope of the present invention, and the scope of patent protection of the present invention should be defined by the claims.

Claims

1. An unsaturated polyester resin, characterized in that The composition comprises the following components by weight percentage: 54.5-59.5% polyester, 35% cross-linking agent, 0.6% fumed silica, 0.0174% accelerator, 0.2% defoamer and the balance surfactant; Wherein, the crosslinking agent comprises styrene and hydroxyethyl methacrylate in a mass ratio of 26:9; The polyester comprises propylene glycol, diethylene glycol, ethylene glycol, phthalic anhydride, maleic anhydride and dicyclopentadiene in a mass ratio of 13.5-16:10:4-6.5:13:9:

5.

2. The method for preparing the unsaturated polyester resin according to claim 1, characterized in that: The steps include: 1) Polycondensing diol, dibasic acid or dibasic acid anhydride with dicyclopentadiene to obtain polyester; 2) The polyester obtained in step 1) is mixed and dispersed evenly with a crosslinking agent, fumed silica and an auxiliary agent to obtain the unsaturated polyester resin.

3. An acrylic composite board with stable surface quality, characterized in that: include: An acrylic plate and a barrier layer and a glass fiber reinforced plastic reinforcing layer adhered to the surface in sequence; wherein the barrier layer and the glass fiber reinforced plastic reinforcing layer contain the unsaturated polyester resin according to claim 1 or the unsaturated polyester resin prepared by the method according to claim 2.

4. The acrylic composite board with stable surface quality according to claim 3, characterized in that: The barrier layer also contains a curing agent and a color paste; the curing agent is added in an amount of 1-5% by weight of the unsaturated polyester resin, and the color paste is added in an amount of 0-20% by weight of the unsaturated polyester resin; the glass fiber reinforced plastic reinforcement layer, in parts by weight, includes the following components: 100 parts by weight of unsaturated polyester resin, 100-140 parts by weight of calcium carbonate powder, 280-320 parts by weight of glass fiber chopped strand mat, and 1-3 parts by weight of the curing agent.

5. The method for preparing an acrylic composite board with stable surface quality according to claim 3 or 4, characterized in that: The steps include: 1) Applying a barrier layer: uniformly mixing the unsaturated polyester resin, the curing agent and the color paste, and applying the mixture on an acrylic plate to prepare a barrier layer; 2) coating a glass fiber reinforced plastic reinforcing layer: the unsaturated polyester resin, calcium carbonate powder and curing agent are mixed and stirred evenly, and glass fiber chopped strand mat is added and mixed evenly to obtain a mixed coating liquid; then the coating liquid is coated on one side of the barrier layer of the acrylic plate obtained in step 1) to obtain a glass fiber reinforced plastic reinforcing layer, and after curing, the acrylic composite plate with stable surface quality is obtained.

6. Use of the acrylic composite board with stable surface quality according to claim 3 or 4 or the acrylic composite board with stable surface quality prepared by the method according to claim 5 in the preparation of decorative boards and sanitary products.

Citation Information

Patent Citations

  • Acrylic composite board for bathroom product and the bathroom product

    CN110435272A

  • Preparation method of wear-resistant self-repairing acrylic material for bathtub

    CN111320730A

  • Method for preparing an acrylic material adhesive resin

    CN101514280A

  • Low-volatization unsaturated polyester resin suitable for large glass steel structural layer and manufacturing method thereof

    CN101613442A

  • Styrene-free unsaturated polyester resin and preparation method thereof

    CN115873179A